Hard driving : the 1908 auto race from New York to Paris - Cole, Dermot, 1953- (Classic reprint series (Fairbanks, Alaska), 2020)
"In the winter of 1908, six cars left Times Square bound for Paris. They were embarking on a remarkable motor race across the world that would capture everyone's imagination. In this book, Dermot Cole weaves a thrilling account of the improbable journey west from New York to Paris, the varied characters, and the nascent automobile industry. Drawing from the drivers' journals and extensive newspaper reports, Cole details the many hardships, triangulations, and physical extremes encountered along the route as the drivers attempted to race from coast to coast, cross the Bering Strait to Russia, traverse Siberia, and onward. Hard Driving delves beyond the headlines that were riveted to the story for six months to explore the race's implications for global politics and diplomacy and how the automobile became a viable mode of transportation"--